Chronic inflammation and extracellular matrix-specific autoimmunity following inadvertent periarticular influenza vaccination. Issue 124 (November 2021) - Hirsiger, Julia R.; Tamborrini, Giorgio; Harder, Dorothee; Bantug, Glenn R.; Hoenger, Gideon; Recher, Mike; Marx, Christian; Li, Quan-Zhen; Martin, Ivan; Hess, Christoph; Scherberich, Arnaud; Daikeler, Thomas; et al.
Abstract: Background: Viral infections may trigger autoimmunity in genetically predisposed individuals. Immunizations mimic viral infections immunologically, but only in rare instances vaccinations coincide with the onset of autoimmunity. Inadvertent vaccine injection into periarticular shoulder tissue can cause inflammatory tissue damage ('shoulder injury related to vaccine administration, SIRVA). Thus, this accident provides a model to study if vaccine-induced pathogen-specific immunity accompanied by a robust inflammatory insult may trigger autoimmunity in specific genetic backgrounds. Methods: We studied 16 otherwise healthy adults with suspected SIRVA occurring following a single work-related influenza immunization campaign in 2017. We performed ultrasound, immunophenotypic analyses, HLA typing, and influenza- and self-reactivity functional immunoassays. Vaccine-related bone toxicity and T cell/osteoclast interactions were assessed in vitro. Findings: Twelve of the 16 subjects had evidence of inflammatory tissue damage on imaging, including bone erosions in six. Tissue damage was associated with a robust peripheral blood T and B cell activation signature and extracellular matrix-reactive autoantibodies. All subjects with erosions were HLA-DRB1*04 positive and showed extracellular matrix-reactive HLA-DRB1*04 restricted T cell responses targeting heparan sulfate proteoglycan (HSPG). Antigen-specific T cells potently activated osteoclasts via RANK/RANK-L, and the osteoclast activation marker Trap5b was high in sera of patients with an erosive shoulder injury. In vitro, the vaccine component alpha-tocopheryl succinate recapitulated bone toxicity and stimulated osteoclasts. Auto-reactivity was transient, with no evidence of progression to rheumatoid arthritis or overt autoimmune disease. Conclusion: Vaccine misapplication, potentially a genetic predisposition, and vaccine components contribute to SIRVA. The association with autoimmunity risk allele HLA-DRB1*04 needs to be further investigated. Despite transient autoimmunity, SIRVA was not associated with progression to autoimmune disease during two years of follow-up. Highlights: Vaccine misapplication can induce chronic inflammatory condition and bone erosions. Erosions associate with HLA-DRB1*04 restricted T cell responses and autoantibodies. The osteoclast activation marker TRAP5b may be a biomarker for SIRVA. Autoimmunity targeted the extracellular matrix protein heparan sulfate glycoprotein. Despite autoreactivity we found no evidence for progression to autoimmune disease.